Poverty reduction and international civil society intervention in Nigeria: A synopsis - Abang, Sunday Owen; Adeforiti, Rotimi; Oni, Kayode Solomon (Universitas Airlangga, 2024)
Poverty is, no doubt, a social phenomenon that cuts across all races, tribes and countries of the world. Where the difference lies is in the varying degrees of poverty in comparative terms, from one country to another. Particularly, the staggering level of poverty in Nigeria is a pointer to perilous times ahead, factoring in the dominant concepts of globalization and liberalization in global economics. The international poverty line was increased from 1 to 1.90 in September 2015, inadvertently pushing more Nigerians below poverty line. The extreme level of poverty in Nigeria is attributable to factors such as bad governance, unequal distribution of the nation's wealth, unemployment, injustice and marginalization, corruption, lack of education, among others. This study adopts structural-functionalism as the analytical framework to examine the effects of various interventions by international civil society organizations in Nigeria, on the level of poverty and the attainment of Sustainable Development Goals (SDGs). In addition, the qualitative method is used to collect data while content analysis was applied on data gathered through secondary method. The study observes that, for the level of poverty to reduce drastically in Nigeria, there is need for good and effective leadership, strong institutions, as well as public-private partnership in public delivery.